Holistic care of a patient with venous ulceration of the leg – a clinical case report - Mościcka, Paulina; Cwajda-Białasik, Justyna; Jawień, Arkadiusz; Szewczyk, Maria T. (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2023)
Venous ulcers of legs are a serious problem for the medical community. According to recommendations, they require first a thorough diagnosis, followed by causal treatment and proper care of the wound and surrounding skin. Long-term disease leads to serious complications, causes unpleasant discomfort and symptoms for the patient, and greatly impairs quality of life, often leading to physical and social limitations. Therefore, the wound hygiene strategy has been incorporated into a holistic model of care for patients with chronic wounds. It pays attention not only to the wound, but also to other factors such as comorbidities, dietary style, mental health, and socioeconomic challenges. This paper presents a case report of a patient with lower limb ulceration, in whom measures in accordance with wound hygiene were implemented.